Synthesis of Nanosilica Originated from Fly Ash using Sol-Gel Method with Methanol as Solvent - Daniel Alvin Chaidir; Hans Kristianto; Arenst Andreas (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Coal fly ash could harm environment and dangerous for human health. Coal fly ash could be used as silica precursor because it contains silica in considerable amount. Method that used to isolate silica is alkaline fusion which used NaOH. The goals are to determine the effect of precursor and solvent ratio (1:9; 1:16; 1:23) and ageing time (3, 6, and 9 days) to particle size and characteristic obtain. Procedure of separating silica begin from burnt fly ash at 750°C, dissolved in HCl, filtered the solution to obtain the precipitate, dried the precipitate and dissolved in NaOH to obtained Na2SiO3. Procedure of nanosilica synthesis was carried out with mixed methanol, water, ammonia, and precursor while stirred for 8 hours, ageing for few days, followed with separate solution using centrifugation method. Product obtained was then characterized using SEM-EDS and XRD. From the results obtained, the ratio of precursor and solvent concentration would affect the particle size obtained and the amount of the product. The highest amount of Si obtained when ratio of precursor : methanol = 1:23 and ageing time 9 days which is 22.64%. Meanwhile, ageing time would affect the particle size distribution obtained. The product also known has amorphous structure.